Modified parallel hybrid heuristic for U.P. Integrated School and U.P. Pampanga timetabling - Avante, Raquel M
This paper uses a parallelized hybrid heuristic, which is parallelizing hybrid genetic algorithm and simulated annealing, as an optimization technique to solve the school timetabling problem with actual data sets coming from the High School Department of the University of the Philippines Integrated School and U.P. Extension Program in Pampanga...